2006
DOI: 10.1177/153244000600600203
|View full text |Cite
|
Sign up to set email alerts
|

Institutions and Representational Roles in American State Legislatures

Abstract: What is the impact of a legislature's institutions on the representational roles its members adopt? We address this question by examining the role orientation of state legislators in eight states, explaining why some legislators identify more with a trustee model of representation and others identify more with the delegate model. Using ordinal logistic regression analysis on data from a survey of 447 legislators, we test for the effects of multimember districts and term limits, along with several other factors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 44 publications
0
15
0
Order By: Relevance
“…While a number of studies have looked at the role orientations of regional legislators (Cooper & Richardson 2006;Freeman & Richardson 1996;Jewell 1982;Wahlke et al 1962), scholarly interest in sub-state legislators has been motivated less by the import of representation at the regional level than by finding as of yet unstudied cases for testing hypotheses (Downs 2014). Like the members of statewide legislatures, regional legislators are elected after having been selected by political parties.…”
Section: Representation At the Regional Levelmentioning
confidence: 99%
“…While a number of studies have looked at the role orientations of regional legislators (Cooper & Richardson 2006;Freeman & Richardson 1996;Jewell 1982;Wahlke et al 1962), scholarly interest in sub-state legislators has been motivated less by the import of representation at the regional level than by finding as of yet unstudied cases for testing hypotheses (Downs 2014). Like the members of statewide legislatures, regional legislators are elected after having been selected by political parties.…”
Section: Representation At the Regional Levelmentioning
confidence: 99%
“…A legislator who acts as a delegate does his or her best to vote on bills in a way that mirrors the preferences of the constituency, while a legislator who acts as a trustee uses his or her own principles and judgment to decide what is best for the district. While we might expect that the smaller size and greater homogeneity of state legislative districts promotes greater adoption of the delegate role at the state level, prior studies indicate state legislators are more likely to see their roles as trustees rather than delegates (Cooper and Richardson 2006;Eulau et al 1959).…”
Section: Fourth Experiment: Delegate Versus Trusteementioning
confidence: 95%
“…There is some empirical work supporting the free-riding hypothesis, but it is not overwhelming. Jewell (1969) and Cooper and Richardson (2006) have found that representatives elected from SMDs are more likely to describe their roles as "delegates," while those elected from MMDs are more likely to describe their roles as "trustees." Scholl (1986) has found a similar pattern in his survey of British (SMD) and French (MMD) members of the European Parliament: British members are more likely to emphasize constituency service and regional issues.…”
mentioning
confidence: 99%